HUBUNGAN KADAR SERUM BRAINDERIVED NEUROTROPHIC FACTOR DENGAN GANGGUAN KOGNITIF PASCACEDERA KEPALA - Restu Susanti,* Yuliarni Syafrita,* Fadil Oenzil** (Neurona Majalah Kedokteran Neuro Sains, 2015)
INTRODUCTION COGNITIVE DYSFUNCTION IS A CHRONIC COMPLICATION OF HEAD INJURY ASSOCIATED WITH THE ABILITY TO REGENERATE CELL PLASTICITY AND LEARNING PROSES BRAINDERIVED NEUROTROPHIC FACTOR BDNF IS ONE OF THE NEUROTROPHIN PLAYING A ROLE IN SYNAPTIC PLASTICITY AND LEARNING PROCESS RESEARCH ON IMPAIRED COGNITIVE FUNCTION AND NEUROGENESIS RESPONSE AFTER ACUTE HEAD INJURIES IS RARE